Problem Based Learning Strategy to Improve Students' Critical Thinking Ability in the Subject of Moral Creeds at MA Al-Khairiyah Pabuaran Cilegon - Aslihah, Aslihah; Eneng Muslihah; Abdul Muin (al-Afkar, Journal For Islamic Studies, 2024)
The motivation behind this research is that if you use a traditional learning model, a learning process that focuses on the role of the teacher can cause less active teaching and learning activities. This reduces students' enthusiasm for learning. In fact, teachers must be able to choose learning models based on the characteristics of the students they teach. The aim of this research is to find out how teachers of the Aqidah Akhlak teaching subject apply the problem-based learning model in class XI MA Al Khairiyah Pabuaran Cilegon. A descriptive approach was used in this research, data collection techniques in the form of observation, interviews, key informants such as moral teaching subject teachers, and supporting informants such as class XI students and school administrators. The results of the research show that students' interest in learning moral beliefs with problem-based learning is considered very good. Students can engage with everyday topics, think critically, and work in groups to solve problems they encounter during learning activities in class.